Reduction of Cogging Torque in Permanent Magnet Flux Switching Motor - Hisham, Siti Fatimah; Sulaiman, Erwan (Evolution in Electrical and Electronic Engineering, 2022)
A high cogging torque is typically the root cause of unwelcome vibration, improper posture, audible noise, and potentially hazardous operating failures. As a result, this thesis proposes a way for reducing the cogging torque using various methods of three phase 12S-10P PMFSM. Notching and chamfering are two of the many methods that have been proposed and examined as potential ways to reduce the amount of torque caused by cogging. The values of the cogging torque were derived as a result of the analysis observation. The analysis was simulated using both machines in order to find the differentiation between them and then compare their results to one another in order to determine which one produced the superior result. From its initial value of 4.263Nm, the cogging torque of a 12S-10P PMFSM was found to be lowered using conventional procedures for Chamfering is 0.088Nm and 0.365Nm for Notching. According to the simulation results, the percentage of cogging torque reduced for notching is 12.18% and 71.05% for chamfering.